'We Want to Live': Metaphor and Ethical Life in F.W. Maitland's Jurisprudence of the Trust. (March 2016) - Gearey, Adam
Abstract : This article argues that reading F.W. Maitland's jurisprudence of the trust alongside Hegel's philosophy of social recognition offers insights into the way in which metaphors 'structure' the modes of ethical life that inform legal and social institutions. Conventional ways of reading Maitland (and John Neville Figgis) have obscured the affinities their work shares with Hegel, and limited the impact of a way of thinking about law and society.